Migration routes and population status of the Brent Goose Branta bernicla nigricans wintering in East Asia - Sawa, Yusuke; Tamura, Chieko; Ikeuchi, Toshio; Fujii, Kaoru; Ishioroshi, Aisa; Shimada, Tetsuo; Tatsuzawa, Shirow; Deng, Xueqin; Cao, Lei; Kim, Hwajung; et al. (Wildfowl, 2020)
Of the world’s Brent Goose Branta bernicla populations, the migration routes and winter distribution of the East Asian population of Brent Geese B. b. nigricans are the least well known. We therefore marked Brent Geese at their primary pre-migratory staging area in Notsuke Bay, Hokkaido, Japan to describe their migration between breeding and wintering areas in East Asia. Additionally, count data were compiled from the literature to identify important wintering and staging sites for the species, following Ramsar Convention criteria, and to assess trends in numbers of Brent Geese recorded in Japan and South Korea. The tracking data provided the first direct evidence of migratory connectivity between staging sites in northern Japan and the Korean Peninsula. A total of 26 internationally important sites were identified in the Russian Far East (7), northern Japan (16), northeast China (2) and the Korean Peninsula (1). Autumn surveys made at staging sites in Japan indicate that the East Asian population is increasing, although more extensive surveys for Brent Geese in China and on the Korean Peninsula are needed to confirm overall population trends and to identify critical habitats and wintering sites. We encourage the continuation of tracking studies, to describe more precisely the main migration routes, staging areas and, importantly, the breeding grounds for this vulnerable Brent Geese population.